The effects of coffee and caffeine consumption on plasma and salivary biomarkers associated with mood in a healthy population - Susan Hall; John W. Yuen; Kyle Hatton-Jones; Shailendra Anoopkumar-Dukie; Devinder Arora; Ben Desbrow; Gary D. Grant (Metabolic Brain Disease, 2025)

Impact of neuroinflammation on brain glutamate and dopamine signalling in schizophrenia: an update - Usha Nayak; Jyothsna Manikkath; Devinder Arora; Jayesh Mudgal (Metabolic Brain Disease, 2025)
Schizophrenia is one of the most severe and chronic psychiatric disorders. Over the years, numerous treatment options have been introduced for schizophrenia. Although they are relatively successful in managing the positive symptoms of schizophrenia, most of the current treatments have a negligible effect on the negative and cognitive symptoms. Thus, none of them could prevent the relapse of psychotic episodes. Among the numerous hypotheses explaining the development and progression of schizophrenia, the cytokine hypothesis explains the role of inflammatory markers as a significant culprit in the development of schizophrenia. Elevated cytokines are reported in animal models and schizophrenic patients. The cytokine hypothesis is based on how increased inflammatory markers can cause changes in the dopaminergic, glutamate, and tryptophan metabolism pathways, like that observed in schizophrenic patients. Reasons, such as autoimmune disease, maternal immune activation, infection, etc., can pave the way for the development of schizophrenia and are associated with the negative, positive and cognitive symptoms of schizophrenia. Thus, there is a need to focus on the significance of anti-inflammatory drugs against these symptoms. The development of new treatment strategies in the management of schizophrenia can provide better therapeutic outcomes in terms of the severity of symptoms and treatment of drug-resistant schizophrenia. This review attempts to explain the association between elevated inflammatory markers and various neurotransmitters, and the possible use of medications like nonsteroidal anti-inflammatory drugs, monoclonal antibodies, statins, and estrogens as adjuvant therapy. Over the years, these hypotheses have been the basis for drug discovery for the treatment of schizophrenia.

Dopamine agonist Rotigotine mitigates lipopolysaccharide-induced neuroinflammation and memory impairment in mice - Prasada Chowdari Gurram; Sairaj Satarker; Ajmal Nassar; Farmiza Begum; Jayesh Mudgal; Devinder Arora; Madhavan Nampoothiri (Metabolic Brain Disease, 2024)

Evaluating the Role of N-Acetyl-L-Tryptophan in the Aβ 1-42-Induced Neuroinflammation and Cognitive Decline in Alzheimer’s Disease - Sairaj Satarker; Prasada Chowdari Gurram; Ajmal Nassar; Suman Manandhar; RJA Vibhavari; Dani Lakshman Yarlagadda; Jayesh Mudgal; Shaila Lewis; Devinder Arora; Madhavan Nampoothiri (Molecular Neurobiology, 2024)
Alzheimer’s disease (AD), a neurodegenerative condition previously known to affect the older population, is also now seen in younger individuals. AD is often associated with cognitive decline and neuroinflammation elevation primarily due to amyloid β (Aβ) accumulation. Multiple pathological complications in AD call for therapies with a wide range of neuroprotection. Our study aims to evaluate the effect of N-acetyl-L-tryptophan (NAT) in ameliorating the cognitive decline and neuroinflammation induced by Aβ 1-42 oligomers and to determine the therapeutic concentration of NAT in the brain. We administered Aβ 1-42 oligomers in rats via intracerebroventricular (i.c.v.) injection to induce AD-like conditions. The NAT-treated animals lowered the cognitive decline in the Morris water maze characterized by shorter escape latency and increased path efficiency and platform entries. Interestingly, the hippocampus and frontal cortex showed downregulation of tumor necrosis factor, interleukin-6, and substance P levels. NAT treatment also reduced acetylcholinesterase activity and total and phosphorylated nuclear factor kappa B and Tau levels. Lastly, we observed upregulation of cAMP response element-binding protein 1 (CREB1) signaling. Surprisingly, our HPLC method was not sensitive enough to detect the therapeutic levels of NAT in the brain, possibly due to NAT concentrations being below the lowest limit of quantification of our validated method. To summarize, the administration of NAT significantly lowered cognitive decline, neuroinflammatory pathways, and Tau protein and triggered the upregulation of CREB1 signaling, suggesting its neuroprotective role in AD-like conditions.

Involvement of NLRP3 inflammasome pathway in the protective mechanisms of ferulic acid and p-coumaric acid in LPS-induced sickness behavior and neuroinflammation in mice - Manas Kinra; Niraja Ranadive; Madhavan Nampoothiri; Devinder Arora; Jayesh Mudgal (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)
Ferulic acid (FA) and p-coumaric acid (PCA) are abundantly present in commonly consumed food and beverages. Being polyphenolic compounds, they have been explored for their antioxidant and anti-inflammatory properties. Based on our previous study, we selected these two compounds to further investigate their potential in lipopolysaccharide (LPS)-induced sickness behavior and the ensuing neuroinflammation by specifically focusing on the NLRP3 inflammasome pathway. Male Swiss albino mice were divided into nine groups (n = 6) consisting of Normal Control, LPS, fluoxetine (FLX), FA40, FA160, FA640, PCA40, PCA160, and PCA640 respectively. Each group received respective FA or PCA treatment except Normal Control and LPS, which received the vehicle, carboxymethylcellulose 0.25% w/v. All groups were challenged with LPS 1.5 mg/kg, intraperitoneally except the Normal Control group, which received saline. Behavioral assessments were performed between 1–2 h, and the whole brains were collected at 3 h post-LPS administration. LPS-induced sickness behavior was characterized by significantly reduced spontaneous activity and high immobility time. The expression of NLRP3, ASC, caspase-1 and IL-1β was significantly increased, along with the levels of brain IL-1β suggesting the assembly and activation of NLRP3 inflammasome pathway. Furthermore, the major cytokines involved in sickness behavior, IL-6 and TNF-α were also significantly elevated with the accompanied lipid peroxidation. The results of this study emphasize that within the employed dose ranges of both FA and PCA, both the compounds were effective at blocking the activation of the NLRP3 inflammasome pathway and thereby reducing the release of IL-1β and the sickness behavior symptoms. There was a prominent effect on cytokine levels and lipid peroxidation as well. Graphical abstract

Involvement of indoleamine 2, 3-dioxygenase (IDO) and brain-derived neurotrophic factor (BDNF) in the neuroprotective mechanisms of ferulic acid against depressive-like behaviour - Sanchari Basu Mallik; Jayesh Mudgal; Manas Kinra; Susan Hall; Gary D. Grant; Shailendra Anoopkumar-Dukie; Madhavan Nampoothiri; Yuqing Zhang; Devinder Arora (Metabolic Brain Disease, 2023)
Objective: Ferulic acid (FA) is a common food ingredient that is abundantly present in various routinely consumed food and beverages. Like many cinnamic acid derivatives, FA produces wide-ranging effects in a dose-dependent manner and various studies link FA consumption with reduced risk of depressive disorders. The aim of this study was to exploit the neuroprotective mechanisms of FA including indoleamine 2,3-dioxygenase (IDO), brain-derived neurotrophic factor (BDNF), and other pro-inflammatory cytokines by employing lipopolysaccharide (LPS)-induced depressive-like behaviour model. Methods: C57BL/6J male mice were divided into 4 groups consisting of saline (SAL), LPS, FA and Imipramine (IMI). Animals were pretreated orally with FA (10 mg/kg) and IMI (10 mg/kg) for 21 days once daily and all groups except SAL were challenged with LPS (0.83 mg/kg) intraperitoneally on day 21. Results: LPS administration produced a biphasic change in the behaviour of the animals where the animals lost a significant weight and express high immobility time at 24 h. Proinflammatory cytokines including, TNF-α, IL-6, IL-1β, and IFN-γ were significantly increased along with increased lipid peroxidation and reduced BDNF. Furthermore, the increased kynurenine to tryptophan ratio was indicative of elevated IDO activity. Conclusion: The results of this study emphasise that low dose of FA is effective in attenuating depressive-like behaviour by modulating IDO, BDNF and reducing neuroinflammation.

Emphasizing the Crosstalk Between Inflammatory and Neural Signaling in Post-traumatic Stress Disorder (PTSD) - Anusha Govindula; Niraja Ranadive; Madhavan Nampoothiri; C Mallikarjuna Rao; Devinder Arora; Jayesh Mudgal (Journal of Neuroimmune Pharmacology, 2023)
Post-traumatic stress disorder (PTSD) is a chronic incapacitating condition with recurrent experience of trauma-related memories, negative mood, altered cognition, and hypervigilance. Agglomeration of preclinical and clinical evidence in recent years specified that alterations in neural networks favor certain characteristics of PTSD. Besides the disruption of hypothalamus-pituitary-axis (HPA) axis, intensified immune status with elevated pro-inflammatory cytokines and arachidonic metabolites of COX-2 such as PGE2 creates a putative scenario in worsening the neurobehavioral facet of PTSD. This review aims to link the Diagnostic and Statistical Manual of mental disorders (DSM-V) symptomology to major neural mechanisms that are supposed to underpin the transition from acute stress reactions to the development of PTSD. Also, to demonstrate how these intertwined processes can be applied to probable early intervention strategies followed by a description of the evidence supporting the proposed mechanisms. Hence in this review, several neural network mechanisms were postulated concerning the HPA axis, COX-2, PGE2, NLRP3, and sirtuins to unravel possible complex neuroinflammatory mechanisms that are obscured in PTSD condition.

Putative involvement of sirtuin modulators in LPS-induced sickness behaviour in mice - Manas Kinra; Niraja Ranadive; Jayesh Mudgal; Yuqing Zhang; Anusha Govindula; Shailendra Anoopkumar-Dukie; Andrew K. Davey; Gary D. Grant; Madhavan Nampoothiri; Devinder Arora (Metabolic Brain Disease, 2022)
NAD + —dependent histone deacetylases (sirtuins 1–7) have been shown to be involved in various pathophysiological conditions including their involvement in cardiovascular, cancerous, neurodegenerative, immune dysregulation and inflammatory conditions. This study investigates the inflammomodulatory potential of resveratrol (RES), a sirtuin activator and sirtinol (SIR), a sirtuin inhibitor in lipopolysaccharide (LPS)-induced model of sickness behaviour in mice. Male Swiss albino mice were divided into five groups (n = 6) consisting of saline (SAL), LPS, RES, SIR, and fluoxetine (FLU) respectively, each group except LPS was prepared by intraperitoneally (i.p.) administration of SAL (10 mL/kg), RES (50 mg/kg), SIR (2 mg/kg) and FLU (10 mg/kg). Thirty minutes after the treatments, all the groups, except SAL were administered LPS (2 mg/kg, i.p.). The behavioural assays including, open field test, forced swim test, and tail suspension tests were conducted 1 h after LPS challenge. LPS administration significantly reduced the locomotor activity along with inducing a state of high immobility and that was prevented by pretreatment with RES and SIR. Further, various proinflammatory cytokines (TNF-α, IL-6, and IL-1β), and oxidative stress markers (MDA and GSH) were found to be significantly elevated in the brain homogenates after LPS treatment. SIR pretreatment abrogated the LPS-induced neuroinflammatory and oxidative stress changes, whereas RES was only effective in reducing the oxidative stress and TNF-α levels. The results of this study speculate that the role of SIRT modulators in neuroinflammatory conditions could vary with their dose, regimen and chemical properties. Further studies with detailed molecular and pharmacokinetic profiling will be needed to explore their therapeutic potentials.

Possible involvement of metformin in downregulation of neuroinflammation and associated behavioural changes in mice - Jayesh Mudgal; Madhavan Nampoothiri; Sanchari Basu Mallik; Manas Kinra; Susan Hall; Gary Grant; Shailendra Anoopkumar-Dukie; C. Mallikarjuna Rao; Devinder Arora (Inflammopharmacology, 2019)

Cannabinoid receptor 2 activation mitigates lipopolysaccharide-induced neuroinflammation and sickness behavior in mice - Puspita Sahu; Jayesh Mudgal; Devinder Arora; Manas Kinra; Sanchari Basu Mallik; Chamallamudi Mallikarjuna Rao; K. S. R. Pai; Madhavan Nampoothiri (Psychopharmacology, 2019)

Interplay between adenosine receptor antagonist and cyclooxygenase inhibitor in haloperidol-induced extrapyramidal effects in mice - Devinder Arora; Jayesh Mudgal; Madhavan Nampoothiri; Sanchari Basu Mallik; Manas Kinra; Susan Hall; Shailendra Anoopkumar-Dukie; Gary D. Grant; Chamallamudi Mallikarjuna Rao (Metabolic Brain Disease, 2018)